ANALISIS PEMBERIAN INSENTIF KARYAWAN DALAM UPAYA PENINGKATAN PIUTANG TERTAGIH PADA PT. RENALTI UTAMA MEDAN - Megawaty Laiya; Mekar Meilisa Amalia (UNIVERSITAS DHARMAWANGSA, 2022)
In an effort to increase receivables collection, incentives are one of the important steps to take because with these incentives it is expected that sales and collectors will work professionally and be motivated to participate in minimizing bad debts. This study aims to determine the provision of employee incentives can increase the amount of receivables that can be billed at PT. Renalti Utama Medan. The type of data used in this research is quantitative data. Sources of data used are primary and secondary data obtained through interviews, observation and documentation. The data analysis technique used is descriptive analysis. The results of the study found that the incentives given to the collection team were quite large, this was seen from the amount of receivables collected in 2020 of Rp. 166,305.673 and in 2021 it is Rp. 159,495,339 and the amount of incentives in 2020 is Rp. 2,804,844.28 and in 2021 a significant increase of Rp. 6,803,742.22 even though the receivables collected decreased in 2021. These incentives play a role in the collection of receivables at PT. Renalti Utama Medan where the total receivables in 2020 are Rp 228,242,214 and collectibles are Rp 166,305.673, in 2021 the total receivables are Rp 246,914,642 and collectibles are Rp 159,495,339. When viewed from the receivables collectible in 2021, the amount decreased and was not significant compared to the previous year. And if it is related to receivables where in 2020 the total receivables are greater than in 2021, it can be concluded that there has been an increase in the total amount of receivables collection because it will be easier to collect them. This has an impact on increasing the incentives provided.